Change of government in Georgia: New emphases in domestic and foreign policy - Sabine Fischer; Uwe Halbach (Stiftung Wissenschaft und Politik (SWP), 2013)
In autumn 2012, Georgia underwent a development that is already being described as historical. Following an emotional and at times hostile election contest, the Georgian parliamentary elections on 1 October led to a change of government, which the country is hailing as proof of its democratic maturity. President Mikheil Saakashvili's United National Movement party, which had been in power for the last nine years and held a two-thirds majority in the last parliament, suffered a clear defeat against a coalition of six opposition parties, none of whom had been represented in the previous parliament. Saakashvili will remain in office until 2013. What course will the new coalition government under Prime Minister Bidzina Ivanishvili now set in domestic and foreign policy? Will the incumbent president, who is endowed with a wide range of powers, and the new government be able to work together in the run-up to the 2013 presidential elections or will they become entrenched in bitter rivalry?
Keywords: 320